Dynamics of halogenesis in ordinary chernozem irrigated with mineralized waters - Nosonenko, O. А.; Zakharova, M. А. (AgroChemistry and Soil Science, 2023)
The purpose of the study is to establish the regularities of the spatial and temporal dynamics of the content of watersoluble salts and the composition of exchangeable cations in ordinary chernozem (Calcic Chernozem) under the influence of irrigation with weakly mineralized water and agromelioration measures in the conditions of a long-term stationary experiment. Methods were used: field - to explore the morphological structure of soil profile, studying the influence of irrigation and agro-melioration measures on the saline and physico-chemical properties of chernozems, laboratory-analytical - to determine saline and physico-chemical parameters, mathematical and statistical - to assess the reliability of research results. Results. Irrigation of ordinary chernozem with weakly mineralized water from the Sasyk reservoir for 12 years led to an increase in the content of water-soluble toxic salts in the soil and a deterioration of their qualitative composition due to the narrowing of the Ca/Na ratio in the soil solution to 10 times and the development of the process of their irrigation sodification. This process is staged: there are stages of sodification and temporary dynamic equilibrium. At the same time, the degree of secondary sodicity gradually increases from weak to strong by the twelfth year of irrigation. The use of chemical melioration (application of phosphogypsum) and the organo-mineral fertilization system limits the process of irrigation sodification (stabilizing it at a weak level). However, it causes accumulation in the root layer of toxic products of cation exchange - toxic salt of sodium sulfate, which causes a weak degree of soil salinization. Conclusions. It was found that under the influence of long-term (12 years) irrigation with weakly mineralized water, the process of irrigation sodification develops in ordinary chernozem, which has a staged character. The use of agro-reclamation measures, first of all, chemical reclamation by applying phosphogypsum and organo-mineral fertilizer system can only limit the process of irrigation sodification, stabilizing it at a low level, but it can cause the development of low-level salinization. Obviously, under the conditions of a seasonally rotating salt regime, the annual application of phosphogypsum at a dose of 3 t/ha for 10 or more years is excessive.